Septic arthritis: what is the role for the rheumatologist? - V. Carraro; M. Favero; F. Schiavon; L. Riato (PAGEPress Publications, 2011)
Septic arthritis (SA) is a clinical emergency with considerable morbidity and mortality that can lead to rapid joint destruction and irreversible loss of function. The reported incidence varies from 2-5 cases per 100.000 individuals per year in the general populations to 70 cases per 100.000 individuals annually among patients with rheumatoid arthritis (RA). Predisposing factors are immunosuppressive and corticosteroids therapy and RA "itself". The expected decrease in incidence of SA was not seen over the last 20 years period but we can, on the contrary, expect an increase in the frequency of its appearance because of the population ageing, the increasingly prosthetic joint replacement, the ability of the bacteria to evade clearance by the host immune response and the rapidly growing number of patients with RA, ankylosing spondylitis and psoriatic arthritis treated with tumour necrosis factor α (TNFα) antagonists. Up to now there have been conflicting reports regarding joint infections in patients under anti-TNF therapy but according to data from Deutsch as well as the British register there might be an increase in the incidence of joint infections in anti TNF treated patients. Microscopic analysis and culture of synovial fluid are fundamental diagnostic tools in the evaluation of possible joint sepsis. Sonographic guidance of arthrocentesis led to successful aspiration of difficultto- access joints as shoulder and hip. There is controversy over which mode of drainage of septic synovial fluid should be employed but needle aspiration appear to be preferable to surgical treatment as an initial mode of treatment of SA. Rheumatologists should have a central role in the diagnosis and management of SA.